1995
DOI: 10.1016/0014-5793(95)01120-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo inactivation of phosphotyrosine protein phosphatases by nitric oxide

Abstract: The effect of NO on phosphotyrosine protein phosphatases (PTPases) has been investigated in vivo. NO production is induced in interferon-y and lipopolyaccharide stimulated RAW-264.7 macrophages as indicated by the increase of NO~ in the medium. Our results demonstrate an inhibition of p-nitrophenylphosphatase activity as a consequence of macrophages activation. Under the described experimental conditions, most of the hydrolysis ofp-nitrophenylphosphate can be ascribed to the action of cellular PTPases. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
3
24
0
1
Order By: Relevance
“…Extracellularly Generated Oxidative Stress-As already reported LMW-PTP is oxidized in vitro by H 2 O 2 and NO (11,12) in its catalytic site cysteines 12 and 17. To study if the generation of an oxidative stress in vivo could lead to LMW-PTP oxidation, thus influencing its catalytic activity, we have used the NIH3T3 fibroblast cell line overexpressing wtLMW-PTP.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringmentioning
confidence: 73%
See 4 more Smart Citations
“…Extracellularly Generated Oxidative Stress-As already reported LMW-PTP is oxidized in vitro by H 2 O 2 and NO (11,12) in its catalytic site cysteines 12 and 17. To study if the generation of an oxidative stress in vivo could lead to LMW-PTP oxidation, thus influencing its catalytic activity, we have used the NIH3T3 fibroblast cell line overexpressing wtLMW-PTP.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringmentioning
confidence: 73%
“…The PTP activity of wtLMW-PTP-expressing cells is strongly inhibited by H 2 O 2 treatment, confirming the results obtained with phosphorylated PDGF-R and p190Rho-GAP. Caselli et al (11,12) have demonstrated that LMW-PTP is oxidized in vitro by both H 2 O 2 and NO and is able to rescue its catalytic activity after treatment with reducing agents. It is interesting to note that further treatment with catalase for 10 min (to remove H 2 O 2 ) led to a complete recovery of LMW-PTP activity ( Fig.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringmentioning
confidence: 99%
See 3 more Smart Citations